A 36‐bp deletion in the alpha subunit of glutamate‐gated chloride channel contributes to abamectin resistance in Plutella xylostella. Issue 2 (30th September 2014) - Liu, Feng; Shi, Xiuzhen; Liang, Yanpo; Wu, Qingjun; Xu, Baoyun; Xie, Wen; Wang, Shaoli; Zhang, Youjun; Liu, Nannan
Abstract Diamondback moth (DBM), Plutella xylostella (L.) (Lepidoptera: Plutellidae), is one of the most destructive pests in Brassicaceae crops, such as Chinese cabbage (Brassica rapa L.). It is rapidly developing resistance to abamectin, the dominant insecticide utilized in controlling P. xylostella in China and other southeastern Asian countries. The target of abamectin, the alpha subunit of glutamate‐gated chloride channel (GluClα), is thought to be involved in the development of abamectin resistance in nematodes and insects. This study investigated variants of GluClα in both abamectin‐susceptible and resistant strains of P. xylostella. A comparison of the PxGluClα sequences revealed three variants, including a 63‐bp substitution, a 36‐bp deletion, and a 65‐bp insertion. The frequency of the 36‐bp deletion was much higher in the abamectin‐resistant strain compared to the susceptible strain, whereas the 63‐bp substitution and 65‐bp insertion showed no significant difference between the resistant and susceptible strains. The in vitro expression of PxGluClα (with or without the 36‐bp deletion) in Xenopus laevis (Daudin) oocytes indicated that PxGluClα with the 36‐bp deletion was less sensitive to both glutamate and abamectin compared to the wild‐type PxGluClα. These findings suggest that the variant 36‐bp deletion in PxGluClα may confer abamectin resistance in P. xylostella after continuous abamectin selection, providing new insights into the management of this pest and contributing to the development of new reagents for pest control.